Profile of Road Traffic Accident Cases Attending in Combined Military Hospital Ramu, Cox’s Bazar (IAHS Medical Journal, 2022)
Background: A Road Traffic Accident (RTA) is any injury due to crashes originating from, terminating with or involving a vehicle partially or fully on a public road. It is one of the leading causes of global disease burden. Road traffic accidents, injuries and fatalities are causing great concern to the community in Bangladesh. To find out the characteristics of road traffic accident cases attending in Combined Military Hospital Ramu, this research work was planned.Materials and methods: This descriptive cross-sectional study was conducted at Combined Military Hospital Ramu.All the road traffic accident victims attending at Medical Inspection room (MI Room) of CMH Ramu from April 2019 to September 2019 irrespective of age and sex . All the victims entered in the ‘special event statement register’. There were 119 Road Traffic Accident victims enlisted and selected by purposive type of sampling technique.Results: Mean age of the respondents was 28.77 ± 5.14 years. Out of 119 respondents, majority (26.9%) were in the age group of 31-40 years. Among the victims, 99.2% were motorized accident. Majority (33.6%) were due to Bus or Minibus accident, 43.8% victims were motor vehicle passenger. The highest 49.6% victims were passenger, followed by 31.9% were pedestrian. Regarding pattern of injury, majority 39.5% victims sustained Laceration and Cut injury. Majority of the accident (50.9%) happened in the main road, 33.6% happened during Noon (1000-1400 hrs) time, followed by 27.7% at afternoon (1400-1800 hrs) time.Conclusion: Among the victims, most of them were male and majority of them were within the active age group. Most of accidents by motorized vehicles by Bus or minibus. Pedestrians and motor vehicle passengers were most vulnerable. Cut injury and Laceration were the most common type of injury. Main roads were the commonest site and accident occurred more during the day.IAHS Medical Journal Vol 4(2), December 2021; 12-16